National Identity in Qatar: A Systematic Literature Review - Logan Cochrane (7822049) (2024)
The Arabian Gulf region has witnessed tremendous social, political and economic change in recent decades. The State of Qatar's ambitious global visions mean that it is a significant player in both creating and riding these transformational waves. Yet with a minority citizen population of only ~12%, protecting the language, culture and values of the nation in the midst of rapid development and modernization presents unique challenges that most governments do not have to grapple with. This has led to strategic and legal stances and policies as well initiatives by governmental and non‐governmental organizations to maintain and develop national identity and Qatari culture. Through a systematic literature review, this paper synthesizes available evidence regarding national identity for Qatari citizens. It explores dominant themes that emerged in the literature related to identity in Qatar, namely: architecture, education and language policy, gender, media and social media, museums, politics and governance, and sports. Each are synthesized, from which we offer reflections on what is (not) known regarding national identity, identifying a number of areas in need of research related to better understanding the complexity and diversity within the citizen population. Other Information Published in: Studies in Ethnicity and Nationalism License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/sena.12417